Complete colonic examination in symptomatic patients with incomplete colonoscopy: it is diagnosed as high-yield - Mohamad, Abdul Malek; Elagili, Faisal; Md Nor, Azmi; Jaafar, Khairul Azhar; Sainal, Mohd. Yusof; Mohammad Aidid, Edre (Lippincott Williams & Wilkins, 2022)
Purpose/Background: Missed lesions are associated with incomplete screening colonoscopy. There is little data on the outcomes of incomplete colonoscopies in symptomatic patients Hypothesis/Aim: To determine the percentage of symptomatic patients who completed a colonic evaluation following an incomplete colonoscopy, how the evaluation was completed, and the incidence of significant pathology Methods/Interventions: All symptomatic patients who had an incomplete colonoscopy between November 2019 and March 2021 were included in a single-center, prospective, observational study. Data on secondary studies offered and their outcomes were gathered. Results/Outcome(s): A total of 207 patients had colonoscopies, with 48 (23 percent) of them being incomplete. Indications include bleeding (45%), bowel habit change (30%), pain (21%), and miscellaneous (4 percent). Previous abdominal surgery, inadequate preparation, and severe pain during the procedure were the most common causes of incomplete colonoscopy. Computed Tomography (CT) colonography was performed in 32 (67%) cases, and repeat colonoscopy was performed in 16 cases (33 percent). In 9 (19%) and 5 (10%) patients, incomplete colonoscopies revealed colorectal carcinoma (CRC) and adenomatous polyps, respectively. Three (60%) of the five adenomatous polyps were considered as advanced adenomas. In total 12 patients were found to have clinically significant lesions (25 percent). Limitations: This study was limited by absence of a control group. Conclusions/Discussion: Our study found that symptomatic patients had a high rate of secondary colonic evaluation, that CT colonography was frequently used for completion, and that significant neoplasia was detected at a high rat